Teori Harga Islami Pandangan Kritis Terhadap Konsep Harga Kapitalis - Thalis Noor Cahyadi (LITERASI (Jurnal Ilmu Pendidikan), 2009)
According to  M. Abdul Mannan in his book  Islamic Economics, Theory and Practice, especially in Chapter VIII describes about how to realize the Islamic price totally  with emphasis on the aspect of needs (needs) to human and human resource. Mannan also describes how to create an Islamic market and an ideal industrial which related  between producers and consumers, including the labor which is then connected to the various factors that influence the price increase.Mannan  price  classifies  into four forms namely the monopoly price, actual price increases,  price increases imitation, and the  price increases caused  by the necessities of life.   Mannan provide advice in the form of  establishment  Wilayatul-hisba  or supervisory agency prices, while on the other hand the need for the establishment of consumer associations who have a bargaining position against the manufacturer, in addition  dialogue method in case of problems between them. The government also felt necessary to make the regulation and supervision of   prices that not harm consumers and society.Keywords: ijtihad, price Islami, Islami work patterns, the dialogue.